ANALISIS PEMAHAMAN MASYARAKAT KOTA BANJARBARU TENTANG BAGI HASIL DAN BUNGA PADA BANK SYARIAH - Masrina, Masrina; Wibowo, Fatria Ulfa (Islamic Economics Program, Faculty of Islamic Economics and Business, 2023)
Conventional banks or Islamic banks can be utilized by the general public. By developing a financial framework that relies on market instruments that are reasonable, useful, fair, independent, and productive, Islamic Banks have a role in public progress in the financial field needed to increase local government assistance, strengthening local areas, and every monetary force, especially for small and medium business visionaries. Qualitative approaches are used to investigate and comprehend the meaning that various individuals or a group of persons attribute to social or humanitarian situations. Typically, small to medium-sized communities are familiar with Islamic banks, especially those living in urban areas. Nevertheless, many people do not understand Islamic banking. In theory, Since normal banks employ an interest system, Islamic banks differ from ordinary banks. While Islamic banks use a profit-sharing system. Despite this, people still do not fully understand Islamic banking